Wildlife conservation and management (Encyclopedia of Bioethics) - Rolston, Holmes, 1932-2025, author; Simon and Schuster, publisher (Colorado State University. Libraries, 1995)
Human activities affect wildlife quite adversely, and humans have duties to care for them, both because of what humans have at stake and also because of what wildlife are in themselves. The main ethical issues in wildlife management (1) the contemporary crisis of conserving historically evolved wildlife populations on rapidly developing human landscapes (2) ownership, control, management, and stewardship responsibilities for wildlife, (3) conservation of endangered wildlife species, (4) fishes and fisheries as managed wildlife populations, (5) wildlife as game for hunting and trapping, including hunting as a conservation strategy, (6) "hands-on" versus "hands-off" management, and (7) feral animals. These are issues of management objectives, but there are ethical questions at every point.
Was republished with title: Wildlife Conservation and Management: Ethical Issues, pages 201-204, volume 1, in Encyclopedia of Bioethics, 3rd ed. Stephen G. Post, Editor-in-Chief (New York: Macmillan Reference/Thomson Gale, 2004).
Rolston served as Area Editor in Environmental Ethics, for the Encyclopedia of Bioethics, Revised Edition.
Keywords: wildlife; wildlife management; ethical concern for wildlife; stewardship; hunting; trapping; feral animals; hands-on; hands-off management